Europe shows first cards in €1-billion quantum bet. (1st November 2018) - Castelvecchi, Davide
One of the most ambitious EU 'Flagship' schemes yet has picked 20 projects, aiming to turn weird physics into useful products. One of the most ambitious EU 'Flagship' schemes yet has picked 20 projects, aiming to turn weird physics into useful products. A view of the stage at the Quantum Flagship Event in Vienna, 28 October 2018